THE ROLE OF WORK MOTIVATION AND WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE: A STUDY AT PT BUKIT BIMA BATARA - Siti Munawaroh; Uce Suganda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of work motivation and work discipline on employee performance at PT Bukit Bima Batara, both partially and simultaneously, as well as to identify the most dominant variable influencing employee performance in a project-based telecommunications company context. This research employed a quantitative approach using multiple linear regression analysis. The population consisted of 163 employees, with a sample of 116 respondents determined using proportional random sampling based on the Slovin formula. Data were collected through structured questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS) version 27. The results indicate that work motivation has a positive but not statistically significant effect on employee performance. In contrast, work discipline has a positive and significant effect and emerges as the most dominant variable influencing employee performance. Simultaneously, work motivation and work discipline significantly affect employee performance. The coefficient of determination (R²) is 0.562, indicating that 56.2% of the variation in employee performance can be explained by work motivation and work discipline, while the remaining 43.8% is influenced by other factors outside the scope of this study, such as leadership, organizational culture, and work environment.